2019
DOI: 10.3390/pathogens8040168
|View full text |Cite
|
Sign up to set email alerts
|

Host Single Nucleotide Polymorphisms Modulating Influenza A Virus Disease in Humans

Abstract: A large number of human genes associated with viral infections contain single nucleotide polymorphisms (SNPs), which represent a genetic variation caused by the change of a single nucleotide in the DNA sequence. SNPs are located in coding or non-coding genomic regions and can affect gene expression or protein function by different mechanisms. Furthermore, they have been linked to multiple human diseases, highlighting their medical relevance. Therefore, the identification and analysis of this kind of polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 166 publications
(250 reference statements)
0
23
0
Order By: Relevance
“…In IAV infections, the most severe responses are associated with 'cytokine storms' or hypercytokinemia. As previously reviewed, 117 SNPs in TNF, CCR5, IL1A and IL1B are associated with susceptibility and severity of influenza infections, although the mechanism by which these SNPs may increase disease susceptibility remains to be fully elucidated. In accordance with possible anti-inflammatory functions of TNF-α, the TNF −238 A allele, which has been demonstrated to correlate with lower TNF transcripts, was overrepresented in IAV pH1N1/09 infected patients in comparison to healthy controls in a Caucasian population.…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
“…In IAV infections, the most severe responses are associated with 'cytokine storms' or hypercytokinemia. As previously reviewed, 117 SNPs in TNF, CCR5, IL1A and IL1B are associated with susceptibility and severity of influenza infections, although the mechanism by which these SNPs may increase disease susceptibility remains to be fully elucidated. In accordance with possible anti-inflammatory functions of TNF-α, the TNF −238 A allele, which has been demonstrated to correlate with lower TNF transcripts, was overrepresented in IAV pH1N1/09 infected patients in comparison to healthy controls in a Caucasian population.…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
“…Other factors may also influence the susceptibility for COVID-19 infected persons, and some gene polymorphisms, well-documented for other viral infections (113).…”
Section: Immune Response and Covid-19mentioning
confidence: 99%
“…As demonstrated for other viral diseases, the basis of these different outcomes there are host predisposing genetic factors leading to different immunogenicity/cytokine responses as well as specific receptor permissiveness to virus and antiviral defence [4][5][6]. Similarly, during the study of host genetics in influenza disease, a pattern of genetic markers has been identified which underlies increased susceptibility to a more severe clinical outcome (as reviewed in [7]). This hypothesis is also supported by a recent work reporting 50% heritability of COVID-19 symptoms [8].…”
Section: Introductionmentioning
confidence: 97%